Design and performance analysis of soil temperature and humidity sensor. Issue 17 (2018) - Shi, W.; Zhang, S.; Wang, M.; Zheng, W.
Abstract: In view of the current soil layer temperature and humidity measurement, there are some problems such as difficult installation and changing soil structure. Therefore the soil temperature and humidity measurement sensor based on high frequency fringe field effect is designed. The measuring principle is based on LC oscillating circuit and soil dielectric constant. Through this method the functional relation between soil humidity and output frequency can be deduced. Numerical analysis technique is used to get the curve of oscillator frequency output with the change of soil humidity. Based on a large number of measured data, the functional relation between output frequency and soil moisture is obtained by data fitting method. Sensors can output data through serial port, GSM and Bluetooth. The soil temperature and humidity sensor is stable through many experiments. It provides an efficient acquisition and measurement method for real-time acquisition of multi-layer soil temperature and humidity.